The Scholarship of Teaching and Learning: Help for Academic Tour Guides - Rachael Saathoff (Park University, 2013)
The presence of scholarship of teaching and learning (SoTL), or its absence, has greatly impacted my undergraduate studies. While professors are experts in their subject matter, they do not always know how to reach students. SoTL provides resources to address such disconnects. Just-in-time teaching (JiTT) is one example of a SoTL-informed teaching assignment that can help students learn more effectively. Because SoTL helps professors understand how students learn, it can encourage excellence in the classroom.